THE INFLUENCE OF THE DEMOCRACY LEADERSHIP STYLE OF THE SCHOOL, TEACHER COMPETENCY AND THE ROLE OF THE SCHOOL COMMITTEE ON THE QUALITY OF HIGH SCHOOL EDUCATION IN TANGERANG DISTRICT - Aryani, Aryani; Susy Suhendra, Euphrasia (Dinasti International Journal of Digital Business Management, 2022)
The purpose of this study was to analyze the influence of the Principal's Democratic Leadership Style, Teacher Competence, and the Role of School Committees on the Quality of Senior High School Education in Tangerang Regency. The success of an organization is determined by students and teachers in operating the work units in the agency. The quality of education can be influenced by several factors, including the Principal's Democratic Leadership Style, Teacher Competence, and the Role of the School Committee. The object of this research is a high school teacher in Tangerang Regency. The sample used is Tangerang Regency Teachers as many as 90 respondents. The analysis used is multiple linear regression. The results of the regression analysis between the Principal's Democratic Leadership Style, Teacher Competence, and the Role of School Committees on Education Quality showed significant results with a significance of 0.046, 0.041 and 0.44 < =0.05. Based on the results of the analysis, it can be concluded that the Leadership Style, Teacher Competence, and the Role of the School Committee have a positive and significant effect on the Quality of Education